COMPUTER METHODS OF CREATING A DIGITAL ARCHIVE OF ARCHITECTURAL MONUMENTS USING 3D SCANNING - Neshchadym, Vladyslav (Theory and practice of design, 2023)
This article examines the concept and importance of digital archives in modern society. The main aspects of digital archives, including their definition, purpose and advantages over traditional archives, are considered in detail. The article also describes the main stages of the process of creating and managing digital archives, including the creation of a digital model, processing, storage and access to digital information. The computer method of digitizing the objects of the architecture of fast obtaining a high-quality digital model (point cloud) of functional tools for reverse design and creation of a digital model on the basis of these models with subsequent analysis and reconstruction and preservation of the house is described in detail. In our work we will be interested in the possibility of using 3D scanning facades for the restoration and conservation of historical objects, as well as for architectural design and reconstruction. The technical aspects of 3D scanning will be considered in detail, including the choice of equipment and software, as well as the importance of processing and analyzing the data received. In the process of scanning, a cloud of points is formed, this is an important component of digital models of objects and parts. They detail the technical aspects of point cloud formation and processing, including the principles of laser or photogrammetric scanning. Integration of electronic files into one search system can be performed using BIM technologies. The abbreviation BIM stands for Building Information Model and is a universal technology that is widely used in the life cycle of a building from the beginning of design to the moment of dismantling. This method of preservation of architectural objects, monuments of architecture will be relevant in wartime, when during hostilities damaged buildings destroyed facades, and sometimes completely destroyed. Purpose. The purpose of the publication is to analyze the method of 3D scanning with the study of the geometric parameters of scan objects, point clouds and their processing, in the process of creating a digital archive of architectural monuments. Methodology. Research 3D scanning involves several key steps and approaches for implementing architectural analysis and creating an electronic library object: 1. Selecting an object of study: selecting a specific object of architecture to be scanned and explored. It can be a building, an architectural monument, a historical object. 2. Scanning equipment and technique: selection and preparation of the necessary equipment for 3D scanning. This could include laser scanners, photogrammetric cameras, GPS systems and other equipment to collect spectacle data. 3. Data collection: conducting an object scanning process to collect point data. It is important to observe high accuracy and quality of data collection to create accurate 3D models. 4. Data processing: processing the resulting point data to create a point cloud or 3D an object model. This step may include noise removal, data equalization, and other processing operations. 5. Analysis and visualization: using the resulting 3D models for architectural analysis and visualization of the object. This may include dimensional measurements, geometry analysis, damage detection, and other aspects. 6. Research and conservation: using the results of the study to determine the needs for the restoration of the object. This may include developing an action plan to preserve the historical value of the object. 7. Data storage: ensuring long-term preservation of the data obtained and 3D models for future research. Creation of a digital archive of monuments and houses, structures. 8. Documentation and reporting: preparation of a report that includes the results of the study, analysis and recommendations for actions with the object. This research methodology will allow architects to carry out detailed analysis and study of objects using modern 3D scanning technologies. Results. As a result of the research, the concept of creating a computer digital archive of architectural monuments using the 3D scanning method has been developed. A step-by-step algorithm of actions is described to quickly obtain a high-quality computer model, after which you can quickly and efficiently analyze the damage and develop a project for the reconstruction and restoration of damaged or lost elements of the facade decoration. Scientific novelty. The method of creating a computer base 3D models of architectural monuments has been developed, with the subsequent possibility of restoration of restoration and technical analysis. Identified problems, and their causes developed an algorithm for solving problems. Practical significance. Creation of a computer model of the relief surface (the whole facade or its part) based on the results of laser 3D scanning makes it possible to accelerate the complex process of restoration and restoration of damaged elements and facade decoration. The possibility of restoration and reconstruction of the facade, through the presence of such a model.